Acquiring infection: the challenges of collecting epidemics and pandemics, past, present and future. Issue 6 (12th October 2021) - Emmens, S.; McEnroe, N.
Abstract : Curators of the history of medicine are now facing one of the greatest challenges of their careers—how to collect and preserve objects that convey the impacts of COVID-19 on science, medicine and wider society, while that same pandemic rages around them. But in such a rapidly changing situation, might looking back help us in going forward? Using the world-famous Medicine collections at London's Science Museum, we will explore how both presences and absences in the museum record can shed light on the challenges and dynamics of collecting around pandemic and infectious diseases, as well as the broader field of public health. Most strikingly, we examine why the 1918–19 Spanish flu pandemic left little material culture behind, in sharp contrast with other epidemic diseases. In recent years, so-called 'rapid response' collecting has become a tool used frequently by museums to capture ongoing developments and current research. To collect COVID-19 presents unique challenges, both practical and ethical, not least because to collect with a view to posterity is an action that remains highly subjective and is dependent on the decisions and personal interests of the curator as well as the influence of major external events.